STUDIES ON EXPERIMENTAL PNEUMONIA : VI. ACTIVE IMMUNITY FOLLOWING EXPERIMENTAL PNEUMOCOCCUS PNEUMONIA IN MONKEYS. - Cecil, Russell L. (The Rockefeller University Press, 1920)
1. Experimental Pneumococcus Type I pneumonia in monkeys confers on them an immunity which protects them against subsequent infection with the homologous type of pneumococcus. The duration of this immunity has not been determined. 2. A certain amount of cross-immunity against the other fixed types of pneumococcus pneumonia may or may not be present following experimental Pneumococcus Type I pneumonia. The degree of cross-immunity is difficult to measure and probably varies widely with the individual monkey. 3. Experimental Pneumococcus Type IV pneumonia in monkeys confers slight if any protection against subsequent infection with the same, or with an homologous strain of Pneumococcus Type IV. 4. There is no evidence in monkeys of cross-immunity against Pneumococcus Type IV pneumonia following Pneumococcus Type I pneumonia; and conversely, Pneumococcus Type IV pneumonia confers no cross-immunity against Pneumococcus Type I pneumonia.